Peran Larutan Kitosan dan Ekstrak Daun Jambu Biji dalam Mempertahankan Kualitas Internal Telur Itik - Sahara, E; Prayuda, B; Sandi, S; Yosi, F; Muslim, G; Triyanto, A (Seminar Nasional Lahan Suboptimal, 2022)
Sahara E, Prayuda B, Sandi S. Yosi F, Muslim G, Triyanto T  2022. The role of chitosan liquid and guava leaf extract  in maintaining the internal quality of duck eggs. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang  27 Oktober 2022. pp. 113-119  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).This study aimed to see the eggs internal quality by soaking of chitosan liquid and guava leaf extract. The study used a completely randomized design (CRD) with 7 treatmens and 4 replication, each replication consisted of two eggs. The treatmens consisted of T0 (without guava leaf extract and chitosan liquid), T1 (immersion with guava leaf extract 0,5%), T2  (immersion with guava leaf extract 1 %), T3 (immersion with guava leaf extract 1,5%), T4 (immersion with 0,5% chitosan liquid ), T5 (immersion with 1% chitosan liquid ), T4 (immersion with 1,5% chitosan liquid ).  The observed variables were egg weight loss, albumen pH, yolk pH and haugh unit. The results showed that the treatment with guava leaf extract and chitosan liquid had a significant effect (P < 0,05) on egg weight loss, albumen pH, haught unit and had no effect on yolk pH (P > 0,05).  The conclusion of this study was that the immersion treatment with chitosan liquid showed lower egg weight loss and albumen pH than other treatments, but a dose of 1,5% chitosan liquid showed a Haugh unit value of 83,89 which was the highest significant (P < 0,05) of all treatmens.